TOXICOLOGICAL STUDY AND QUANTITATIVE DETERMINATION OF ALLURA RED (E129) DYE ADDITIVE IN SOME FOOD BEVERAGES CONSUMED IN KATSINA METROPOLIS, NIGERIA - Lawal, Abubakar; Abdulkarim, Suraj (FUDMA JOURNAL OF SCIENCES, 2024)
The continuous use of synthetic dyes in beverage foods as additives for consumers’ attraction could lead to many health-related issues that include cancer, allergic reactions etc. These have leads to urgent monitoring of the amount of such colorants in foods and beverages. Experimentally, the acute toxicity (LD50) was carried out on the Allura red (E129) dye using wistar albino rats in accordance with the administered doses per body weight of the tested animals, as well as quantitative determination of the dye analyte in some food beverages consumed in Katsina metropolis, Nigeria. However, the quantitatively analyzed samples were found to contain 115.294 ± 0.013, 109.142 ± 0.115, 117.173 ± 0.037, 118.385 ± 0.080 and 123.203 ± 0.051 mg/L of the Allura red (E129) dye in sample A, B, C, D and E, respectively. Also, the LD50 result of the Allura red (E129) dye standard was estimated to be more than 5000 mg/L per body weight of the tested animals. Even though, there are few changes in the animals’ behavioral attitudes, which vary according to the concentration of doses administered and the results produced no mortality at the given doses range of 50 to 5000 mg/L after administering the dye standards. Therefore, the results justify the unsafe consumption of the analyzed beverages since the concentration of the Allura red (E129) azo dye in them is above the maximum permissible limits of 50 mg/L as supported by the Guideline for the Testing of Chemicals, Acute Oral Toxicity–Acute Toxic (OECD, 2001).